Teknis Pembayaran Melalui Transfer Rekening - Kholishudin Kholishudin; Abdulloh Arif Mukhlas (Journal of Islamic Banking, 2022)
If the procedures in the transaction process have not been fulfilled, it will affect the perfection of the transaction. If it is still injured, then there is a legal disability. In the sale and purchase agreement, if the handover cannot be carried out, then the sale and purchase law is invalid, if the handover has not been carried out, then the sale and purchase is not perfect, if the handover method is wrong, then there is a legal defect. Handover in buying and selling in modern times has developments that are far different from the handover that occurred in the past, although the handover method as practiced by people in the past is also still found. In the past, handover in buying and selling was only done manually or handover directly or by yadan bi yadin, whereas in today's online era it is common for handovers to occur via delivery services and payments via transfer to an account. The implementation practice is clearly different, but whether the legal influence has a different effect. This paper discusses the handover of ma'qud alaih and its legal implications and focuses more on the technicalities of payment by transfer.